Czy Jan Kott stworzył mit? Jeszcze raz o „Hamlecie” ‘56 Romana Zawistowskiego - Świątkowska , Wanda (Annales Universitatis Paedagogicae Cracoviensis | Studia Historicolitteraria, 2019)
The article presents the origins of Hamlet directed by Roman Zawistowski at the Stary Theatre in Krakow (1956) and is an attempt at answering the question: to what extent the famous Jan Kott’s review influenced its reception. The author analyzes the translation of the tragedy, the script of the play, acting, scenography and the historical context. By comparing the reviews with Kott’s interpretation, it is possible to indicate the areas where critics disagree, and at which point Kott’s review becomes opinion-oriented and establishes the reception of Zawistowski’s Hamlet - actually to this day.